Iron tailings/ammonium polyphosphate system in rigid polyurethane foam composites to enhance fire safety: a novel strategy for utilization of metallurgical solid waste. Issue 10 (14th May 2022) - Wang, Hao; Xu, Zicheng; Yang, Yadong; Liu, Mengru; Yang, Sujie; Wang, Bibo; Deng, Dan; Liu, Xiuyu; Tang, Gang
Abstract: Iron tailings (ITs) is a solid waste after mineral processing, but the high value utilization of ITs has always been a problem perplexing the industry. In order to broaden its application field, it was compounded with ammonium polyphosphate (APP) to make rigid polyurethane foam flame retardant. SEM, limiting oxygen index, UL‐94 vertical combustion, TGA, the cone calorimetry test (CCT), thermogravimetric analysis‐Fourier transform infrared spectroscopy (TG‐FTIR) and Raman tests were used to characterize the bubble morphology, flame retardant properties, thermal stability, combustion performance, gas phase products and graphitization degree of the char layer. The TGA indicated that ITs/APP could effectively improve the thermal stability of the composites, and the T 5wt% of the composites and the char residue rates at 700 °C were significantly improved. The CCT confirmed that ITs/APP could effectively reduce the thermal damage and non‐thermal damage of the composites, and the peak heat release rate, total heat release and smoke factor were reduced by 29.08%, 19.21% and 36.69%, respectively. The TG‐FTIR test implied that ITs/APP inhibited the release intensity of various gaseous products. The CCT, SEM and Raman tests showed that ITs/APP improved the compactness and graphitization degree of the char residue of the composites, thus improving their flame retardancy. This study provides a theoretical basis and experimental basis for the high value utilization of ITs. © 2022 Society of Industrial Chemistry. Abstract : In order to broaden the application field of iron tailings, they were compounded with ammonium polyphosphate to make rigid polyurethane foam (RPUF) flame retardant. The composites' bubble morphology, flame retardant properties, thermal stability, combustion performance, gas phase products and graphitization degree of the char layer were investigated systematically.